2018
DOI: 10.1515/med-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of Highly Injectable Bi-Phasic Bone Substitute (CERAMENT) in the treatment of benign bone tumors and tumor-like lesions

Abstract: AbstractBackground: CERAMENT™|BONE VOID FILLER is an injectable and moldable ceramic bone substitute material intended for bone voids. The material consists of hydroxyapatite and calcium sulfate hemihydrate. The aim of this study is to present the first long-term results following open curettage of benign bone tumors and tumor-like lesions and void filling with this novel injectable and synthetic bone graft. Methods: Thirty three patients were enrolled into the study between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…Although HA/CaS compound is naturally radiopaque, the manufacturer states CERAMENT -the bone gra substitute used in our study -provides enhanced radiopacity due to radiopaque agent iohexol. e claim is backed by two authors reporting good perioperative radio visibility of the void ller during the operation [8,15]. Surgeons state other advantages of its users such as reliable injectability, early unrestricted activity, and fast remodeling to bone [8,12,15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although HA/CaS compound is naturally radiopaque, the manufacturer states CERAMENT -the bone gra substitute used in our study -provides enhanced radiopacity due to radiopaque agent iohexol. e claim is backed by two authors reporting good perioperative radio visibility of the void ller during the operation [8,15]. Surgeons state other advantages of its users such as reliable injectability, early unrestricted activity, and fast remodeling to bone [8,12,15].…”
Section: Resultsmentioning
confidence: 99%
“…e claim is backed by two authors reporting good perioperative radio visibility of the void ller during the operation [8,15]. Surgeons state other advantages of its users such as reliable injectability, early unrestricted activity, and fast remodeling to bone [8,12,15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of different inorganic materials, inorganic and organic, inorganic materials, and bone induction factors as well as organic materials and bone induction factors has gradually appeared. Kotrych et al ( 105 ) reported that the application of Highly Injectable Bi-Phasic Bone Substitute (CERAMENT) achieved good clinical effects. Hattori et al ( 106 ) found that HA/TCP was more bioresorbable and osteoconductive than HA or AWGC.…”
Section: Review and Findingsmentioning
confidence: 99%